Innovation in Curriculum: Merdeka Curriculum and its Implementation - Luthfi Yasykur Luthfi; Teti Muliawati; Qiqi Yuliati Zaqiah (STAI Miftahul Ula Nganjuk, 2023)
This research is motivated by the importance of implementing a new curriculum and aims to analyze the implementation of the independent curriculum at SMAIT Miftahul Khoir Bandung. This research method uses qualitative research with a case study research type. The focus of this research is at SMAIT Miftahul Khoir Bandung and the focus of this research is to analyze the implementation of the independent curriculum at SMAIT Miftahul Khoir Bandung. The data sources used in this study are primary data (school principals, teachers, and parties who can provide information) and secondary data (data already in the school in the form of documents, learning tools, and so on). Data analysis techniques using observation, interviews, and documentation. The research results show 1) The concept of an independent curriculum is an idea that carries the vision of freeing the curriculum from dependence on an established education system that seems rigid and has too many rules. 2) Implementation of the independent curriculum at SMAIT Miftahul Khoir Bandung through 4 approaches namely; a. Intracurricular Curriculum, in which the management system uses a regular system, a block system, a collaboration system, and a class transfer system. b. Project to strengthen the profile of Pancasila students. c. Extracurricular. 3) The problems faced by SMAIT Mifathul Khoir Bandung are that not all teachers respond quickly to curriculum changes so the independent curriculum is considered more difficult and troublesome, teachers have not been able to develop students' creativity as expected, lack of teacher innovation in the learning process, lack of facilities and infrastructure school.